Urbi et Orbi : uma análise da programação televisual de duas emissoras de TV católicas Canção Nova e TV Aparecida - Custódio, Flávio Maia (2013)
The Catholic Church elected the last decade of the past century for the investment in television as a resource and mean for evangelization, consolidating its tradition in electronic evangelization, started on the radio in the 50 s. Currently, in Brazil, there are four coexisting catholic television stations, which broadcast nationally: Rede Vida, Canção Nova, TV Século XXI and TV Aparecida, besides the local ones maintained by dioceses. The investment in television means that the physical church itself is no longer the exclusive place for the expression of cult. Our object of study is the analysis of the televisual broadcast produced by two catholic television stations: TV Canção Nova and TV Aparecida. The choice of these stations was made due to the definition of two distinct scenarios of Catholicism: the charismatic scenario and the institutional scenario. Two weeks were randomly selected during the research for an accurate analysis of the broadcast. We will take into consideration for the analysis not only the technical characteristics of the audiovisual but, above all, the content aired. We avoided the comparative analysis between the two stations because it would be irrelevant, considering that both are confessional stations of the same creed. We intend to verify if there is any differential between the broadcast produced by these stations and the others, basing on the hypothesis that by absorbing several formats of radiophonic programs and transposing them to television, confessional Catholics prepare its programming plan in formats that have already been established by evangelization and repeat in their broadcast the formats from nonconfessional stations. Our analysis is based on the case study of the mentioned stations and is supported by theories of cultural miscegenation (GRUZINSKI, 2001; PINHEIRO, 2009); of cultural mediation (MARTIN-BARBERO, 2001, 2004); the spectacle society (DEBORD, 2007); the sociology of absences and the emergencies (SANTOS, 2010)